Assessing veterinary professionals’ perspectives on community knowledge, attitudes, and practices regarding dog rabies in Turkana, Kenya - Das, Moumita; Aguirreburualde, María Sol Pérez; Kipkemoi, Job Ronoh; Nakadio, Erenius Lochede; Perez, Andres M.; Wilkins, Melinda (Frontiers in Veterinary Science, 2025)
In Kenya, rabies is a deadly zoonotic illness that has been recognized for over a century. The main reservoir and vector for human transmission of the disease is domestic dogs. Utilizing a Rabies Workshop in Turkana County, Kenya in November 2023, this study aimed to assess the knowledge, attitudes, and practices (KAP) of the local community people regarding rabies. Data were gathered using an online survey from a range of veterinary professionals, including public and private veterinarians, para-veterinarians, and community disease reporters, using a cross-sectional approach. Each participant acted as a representative respondent for the local communities in which they served. A one-way analysis of variance (ANOVA) was used to analyze occupational differences, while a two-sample t-test was conducted to evaluate regional differences. The results indicated that 42.4% of experts believed less than half of the community was knowledgeable about rabies, while 75.8% thought less than half could recognize the clinical signs in dogs. Likewise, the level of knowledge, positive attitudes, and practices regarding dog vaccination in Turkana was similarly less than 50%. Dogs were largely utilized for the purpose of security and guarding, and predominantly free to roam. The primary obstacles to dog vaccination encompassed insufficient awareness regarding rabies, a lack of information concerning immunization campaigns and the cost of vaccination. No statistical significance was found in the participant’s responses against their service locations, and their professions, except the positive attitudes toward veterinary care for dogs in different sub-counties (p-value = 0.03). The study indicates that utilizing any and/or all professionals can contribute valid surveillance data for rabies control efforts in Turkana. Overall, the rabies-related knowledge, attitudes, and practices among the Turkana community are unsatisfactory across all sub-counties. These findings have significant influence on policy development and decision-making process, highlighting the importance of targeted interventions to improve rabies awareness and vaccination rates in similar settings.